EFFECTIVENESS OF ANTHOCYANIN AS A HEPATOPROTECTOR: A SYSTEMATIC LITERATURE REVIEW - Amanda Putri, Khairunnisa Rizqika; Lusiana, Evi; Theodorus; Rosdah, Ayeshah Augusta; Harahap, Debby Handayati; Larasati, Veny (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Exposure to free radicals can cause hepatotoxicity in liver cells. Hepatoprotectors are needed to prevent free radicals. The flavonoid group anthocyanin compounds, which give many plants purple, blue, and red colors, have antioxidant activity as hepatoprotectors. This study uses a systematic literature review to review the effectiveness of various plants containing anthocyanins as hepatoprotectors. Articles were searched using Google Scholar, PubMed, and NCBI with keywords such as "Anthocyanin compounds and Hepatoprotective effects" that met the inclusion and exclusion criteria. The results obtained from 7 review articles show that several plants contain anthocyanins, such as bilberry and blackberry, Rosella, purple cabbage, butterfly pea flower, Aronia melanocarpa Elliot (AMA), red cabbage, and radish. The mechanisms in plants containing anthocyanins as hepatoprotective include antioxidant activity, inhibition of cytochrome enzymes, inhibition of inflammation, protein expression, and modulation of the apoptotic signal pathway. This review concludes that plants containing anthocyanins are effective as natural hepatoprotectors with various mechanisms.